UNIT AUTOMATIC MAIN FAILURE (AMF) POWER SYSTEM SEBAGAI SARANA UP-DATING KOMPETENSI GURU-GURU SMK JURUSAN LISTRIK - Zamtinah FT; Djoko Laras BT; Herlambang SP; Didik Hariyanto (Jurnal Kependidikan, 2009)
Prediction of electrical energy crisis in Indonesia clearly will cause losses for electricity consumers. The impact caused the activities disturb include production systems, loss of business opportunities, and loss of property intellectuals (for example, data lost), especially for the scientists and academics. Customers require backup supply of electricity when PLN have some trouble. However, switching supplies electricity to Genset, if done in a conventional addition that requires the existence of the operator, but also through a complex procedure and takes a long time. Therefore need to use an automation tool that supplies electricity more practical and economical, and can be used as a medium of education, and will solve the problem of scarcity of human resources automation field, such as the electricity supply at this time. Expected performance of these tools is able to activate the genset manually or automatically in case of interruption of supply electricity, the Power Loss, Under Voltage, Lower Voltage, frequency interference. All activities since the design to the test conducted in the Laboratory of Electrical Installation and Laboratory Data Communications, Department of Educational Electrical Engineering FT UNY. The method of this experiment is a Research and Development, and experimental data taken according to the research instrument. The data obtained and analyzed using descriptive. The result that activity is the Unit of AMF Power System based on microcontroller that is ready as a medium of education, both in the Department of Educational Electrical Engineering FT UNY and Technical High School. However, this tool only can detect the interference of Under Voltage and Upper Voltage, while the interference of frequency and the condition of fuel can not be carried out due to various technical constraints. Alamat Korespondensi: Zamtinah Jurusan Pendidikan Teknik Elektro-Fakultas Teknik Universitas Negeri Yogyakarta. Karangmalang Yogyakarta. 55281. HP. 081328797306 e-mail: buzam@telkom.net Keywords: AMF, Competence Update, Electrical